PENGEMBANGAN USAHA DESA WISATA RELIGI DI DESA TUYUHAN KECAMATAN PANCUR KABUPATEN REMBANG - Binti Nurrohimah; Rikah Rikah; M. Kelvin Zudhianshah; Ming Ming Lukiarti (Universitas YPPI Rembang, 2022)
Mentoring is an activity in community empowerment by placing assistants who act as facilitators, communicators, and dynamists. In this case, service assistance with Pokdarwis in Tuyuhan Village, Pancur District, Rembang Regency. The problems faced by Pokdarwis include the lack of popularity of Maqam Mbah Djumali, no list of attendance books for pilgrims, no genealogy that explains the history of Maqam Mbah Djumali, no Pokdarwis google account and social media accounts, and the location of Maqam Mbah Djumali is not yet available. registered.Based on these problems, the implementing team made a program plan to introduce the existence of Maqam Mbah Djumali, namely by carrying out marketing carried out through online media, making attendance lists for pilgrims, making genealogies that explain the history of Maqam Mbah Djumali, creating gmail accounts, creating accounts. Instagram social media, to registration of business locations on Google Maps.The results of the program implementation by the implementing Team with Pokdarwis are making an attendance list for pilgrims, making banners, creating a Pokdarwis google account, creating Instagram social media accounts as marketing media, and registering business locations on google maps to make it easier to find addresses.Keywords: Mentoring, Pokdarwis, and Maqam Mbah Djumali.